Records management for dummies - Richardson, Blake (John Wiley & Sons, Inc., 2012)
With proper electronic data management, your business can lower costs, improve efficiency, eliminate duplication, and be protected in the event of a lawsuit. Richardson provides an overview of records management solutions and implementation strategies in plain, non-technical English.